PERAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU TENAGA PENDIDIK DI MTS NEGERI 1 LAMPUNG SELATAN - Yola Arjunita Putri; Ahmad Fauzan; Fisman Bedi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to describe the Role of Madrasah Heads in Improving the Quality of Educators. This research is a qualitative research using observation, interview and documentation methods. In this case, by understanding the role of the head of the madrasah in improving the quality of educators, how the role is carried out to improve the quality of educators. This study used interview and observational data collection techniques. Primary data is obtained directly from respondents regarding the role of madrasah heads in improving the quality of educators, while secondary data in the form of legal theories and norms and other supports are obtained from literature, documentation. All of these data are materials to describe the role of madrasah heads in improving the quality of educators. The results showed that the development of professionalism of educators is one way to improve the quality of education, because the quality of an education, one of which is determined by the quality of educators’ resources. Indicators in terms of the role of a madrasah head to improve the quality of educators are inspiring educators to innovate, motivating educators in carrying out their duties and responsibilities, shaping the behavior of educators, providing training and guidance, supervising learning programs.